2018
DOI: 10.1055/s-0038-1672120
|View full text |Cite
|
Sign up to set email alerts
|

Outcome after Combined Lateral Extra-articular Tenodesis and Anterior Cruciate Ligament Revision in Professional Soccer Players

Abstract: We report the functional outcome after combined anterior cruciate ligament (ACL) reconstruction and lateral extra-articular tenodesis (LET) for ACL re-rupture and high-grade pivot shift in professional soccer players. For this retrospective review, the medical records of 24 professional soccer players were analyzed. The mean age at surgery was 23.8 ± 4.2 years and the mean follow-up was 42.2 ± 16.9 months. Pre- and postoperative assessment included the KT-1000 Lachman test, pivot shift test, International Knee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 25 publications
0
45
2
1
Order By: Relevance
“…Data on 818 patients, including 407 who underwent ACLR+LET and 411 who underwent ACLR, were pooled from 4 studies 4,18,45,46 that reported the postoperative side-to-side difference as measured using a KT-1000/-2000 arthrometer (Figure 6). At last follow-up, this measurement was not significantly different between the 2 groups (SMD, –0.43 [95% CI, –0.95 to 0.09]; P = .11), although heterogeneity was high for this outcome ( I 2 = 88%; P < .00001).…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…Data on 818 patients, including 407 who underwent ACLR+LET and 411 who underwent ACLR, were pooled from 4 studies 4,18,45,46 that reported the postoperative side-to-side difference as measured using a KT-1000/-2000 arthrometer (Figure 6). At last follow-up, this measurement was not significantly different between the 2 groups (SMD, –0.43 [95% CI, –0.95 to 0.09]; P = .11), although heterogeneity was high for this outcome ( I 2 = 88%; P < .00001).…”
Section: Resultsmentioning
confidence: 88%
“…The results revealed no significant differences in terms of positive anterior laxity between the ACLR+LET and ACLR groups (RR, 0.76 [95% CI, 0.48-1.21]; P = .26). There was low to moderate heterogeneity among the studies ( I 2 = 40%; P = .17).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Two failures occurred; one was caused by a new traumatic event and a second by septic arthritis. The rate of return to sport (at the same level) was 91.7% and the average time from surgery was an average of 9.2 months [15]. Guzzini et al [22] showed similar results in 16 elite female soccer players undergoing primary ACLR + LET.…”
Section: Lateral Extra-articular Tenodesis Proceduresmentioning
confidence: 82%